Sigma-1 Receptor Inhibition Reduces Neuropathic Pain Induced by Partial Sciatic Nerve Transection in Mice by Opioid-Dependent and -Independent Mechanisms - Bravo-Caparrós, Inmaculada; Perazzoli, Gloria; Yeste, Sandra; Cikes, Domagoj; Baeyens, José Manuel; Cobos, Enrique José; Nieto, Francisco Rafael (Frontiers in Pharmacology, 2019)
SiSigma-1 (σ1) receptor antagonists are promising tools for neuropathic pain treatment, but it is unknown whether σ1 receptor inhibition ameliorates the neuropathic signs induced by nerve transection, in which the pathophysiological mechanisms and response to drug treatment differ from other neuropathic pain models. In addition, σ1 antagonism ameliorates inflammatory pain through modulation of the endogenous opioid system, but it is unknown whether this occurs during neuropathic pain. We investigated the effect of σ1 inhibition on the painful hypersensitivity associated with the spared nerve injury (SNI) model in mice. Wild-type (WT) mice developed prominent cold (acetone test), mechanical (von Frey test) and heat hypersensitivity (Hargreaves test) after SNI. σ1 receptor knockout (σ1-KO) mice did not develop cold allodynia and showed significantly less mechanical allodynia, although they developed heat hyperalgesia after SNI. The systemic acute administration of the selective σ1 receptor antagonist S1RA attenuated all three types of SNI-induced hypersensitivity in WT mice. These ameliorative effects of S1RA were reversed by the administration of the σ1 agonist PRE-084, and were absent in σ1-KO mice, indicating the selectivity of S1RA-induced effects. The opioid antagonist naloxone and its peripherally restricted analog naloxone methiodide prevented S1RA-induced effects in mechanical and heat hypersensitivity, but not in cold allodynia, indicating that opioid-dependent and independent mechanisms are involved in the effects of this σ1 antagonist. The repeated administration of S1RA twice a day during 10 days reduced SNI-induced cold, mechanical and heat hypersensitivity without inducing analgesic tolerance during treatment. These effects were observed up to 12 hours after the last administration, when S1RA was undetectable in plasma or brain, indicating long-lasting pharmacodynamic effects. These data suggest that σ1 antagonism may have therapeutic value for the treatment of neuropathic pain induced by the transection of peripheral nerves.